Impact of Country Risk and Return on FPI - Ahmed Al Samman; Mostafa Kotb GabAlla (International Journal of Economics and Financial Issues, 2020)
This study measures the economic content of three different inductors of country risk: political, economic and financial risk indices, and fundamental attributes, such as earning-to-price ratios, and its impact on net foreign portfolio equity investment inflow in Egypt. We explore whether any of these measures contain information about net foreign portfolio equity investment inflow in Egypt. The study uses the autoregressive distributed lag (ARDL) bounds testing approach. Quantitative estimates based on the time series annual data from 2004 to 2018. The empirical results prove that there is a univariate cointegrated and stable long-run relationship among net foreign portfolio equity investment inflow and three different measures of country risk and E/P ratio. The results show that three measures of country risk have a significant effect on net foreign portfolio equity investment inflow in Egypt in the long and short run. But Political risk is a positive effect, While Economic and Financial risks are a negative effect. And E/P ratio has a positive significant effect on net foreign portfolio equity investment in Egypt in the short run only. The results confirm that after Procedure the CUSUM and CUSUMSQ tests, net foreign portfolio equity investment inflow function is stable.